2013
DOI: 10.1039/c2nr33637e
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse gold–palladium alloy nanoparticles and their composition-controlled catalysis in formic acid dehydrogenation under mild conditions

Abstract: Monodisperse 4 nm AuPd alloy nanoparticles with controlled composition were synthesized by co-reduction of hydrogen tetrachloroaurate(III) hydrate and palladium(II) acetylacetonate with a borane-morpholine complex in oleylamine. These NPs showed high activity (TOF = 230 h(-1)) and stability in catalyzing formic acid dehydrogenation and hydrogen production in water at 50 °C without any additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(113 citation statements)
references
References 37 publications
(8 reference statements)
2
108
0
3
Order By: Relevance
“…The enhancement in electrocatalytic activity of alloys, as compared to pure metal constituents, has also been recognized for many non‐platinum metals including gold and palladium . For instance, palladium is a platinum‐group metal that binds to oxygen even more strongly than platinum, whereas gold has very little interaction with oxygen, making these two metals optimal candidates for a binary alloy .…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement in electrocatalytic activity of alloys, as compared to pure metal constituents, has also been recognized for many non‐platinum metals including gold and palladium . For instance, palladium is a platinum‐group metal that binds to oxygen even more strongly than platinum, whereas gold has very little interaction with oxygen, making these two metals optimal candidates for a binary alloy .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As one of the most studied bimetallic systems, Pd−Au catalysts have displayed promising performance for a broad range of catalytic reactions such as CO oxidation, [3][4][5] acetoxylation of ethylene to vinyl acetate, 6,7 selective oxidation of alcohols, [8][9][10][11] selective hydrogenation of unsaturated hydrocarbons, [12][13][14][15] hydrodechlorination of chlorinated compounds, [16][17][18] hydrodesulfurization of sulfur-containing molecules, 19,20 decomposition of liquid hydrocarbons for H 2 production, 21,22 and the direct synthesis of H 2 O 2 from H 2 and O 2 . 1,2 As one of the most studied bimetallic systems, Pd−Au catalysts have displayed promising performance for a broad range of catalytic reactions such as CO oxidation, [3][4][5] acetoxylation of ethylene to vinyl acetate, 6,7 selective oxidation of alcohols, [8][9][10][11] selective hydrogenation of unsaturated hydrocarbons, [12][13][14][15] hydrodechlorination of chlorinated compounds, [16][17][18] hydrodesulfurization of sulfur-containing molecules, 19,20 decomposition of liquid hydrocarbons for H 2 production, 21,22 and the direct synthesis of H 2 O 2 from H 2 and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts are generally more stable but much less active than the homogeneous ones. [9] Encouraged by this result, we further improved our solution phase synthesis and produced monodisperse 2.2 nm AgPd NPs with the desired composition controls. [4] For example, AgPd NPs supported on cerium oxide or AuPd NPs immobilized in a metal-organic framework showed an enhanced FA dehydrogenation catalysis with the initial turnover frequency (TOF) reaching 210 h À1 or 192 h À1 at 90 8C, respectively.…”
mentioning
confidence: 96%
“…[9] Encouraged by this result, we further improved our solution phase synthesis and produced monodisperse 2.2 nm AgPd NPs with the desired composition controls. Our very recent report showed that monodisperse 4 nm AuPd NPs were more active in catalyzing the dehydrogenation of FA in water at 50 8C without using any additive and their initial TOF reached 230 h À1 .…”
mentioning
confidence: 96%